Adaptação e resiliência da cadeia de valor da carne bovina: impactos da covid-19, comportamento de consumo e estratégias competitivas - Ramser, Claudia Aline de Souza (2024)
This study examines the demand for beef and discusses how the COVID-19 pandemic has impacted the beef value chain, exploring economic dynamics and companies' adaptive capacity in a globalized market. The study is divided into three articles. The first aims to identify, through a bibliographic review and bibliometric analysis, effective strategies for addressing the challenges imposed by the recessionary crisis triggered by the pandemic, as well as potential future crises. The second article empirically investigates how companies within global food value chains (GFVC) reimagine their business structure in response to COVID-19. Through the translation and adaptation of a questionnaire, a web survey was conducted, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the interrelations among proposed dimensions. The third article analyzes Brazilian consumption behavior regarding beef, considering the Broad Consumer Price Index (IPCA) and the average income of the Brazilian population. To understand consumer behavior, detrended fluctuation analysis (DFA) and detrended cross-correlation analysis (DCCA) will be utilized. Ultimately, the results contribute to an in-depth understanding of the challenges and opportunities within the beef value chain, especially in times of crisis, and offer valuable recommendations for strengthening the sector’s resilience and competitiveness.